Effects of MoS2 and WS2 on the matrix performance of WC based impregnated diamond bit. (March 2019) - Tan, Songcheng; Zhang, Wenjiao; Duan, Longchen; Pan, Bingsuo; Rabiei, Minou; Li, Chenglong
Abstract: MoS2 and WS2 with different concentrations were added to a hot-pressing WC based impregnated diamond bit matrix, in order to investigate the effects of the solid lubricants on the mechanical, wear and frictional properties of the self-lubricating composites. Hardness, flexure strength, impact toughness, abrasion weight loss and coefficient of friction were measured by a series of tests. Also, the full broken section morphologies of the self-lubricating composites after the flexure strength test, as well as the wear surfaces were observed and analyzed by scanning electron microscope. Test results indicate that the effects of MoS2 and WS2 on the mechanical, wear and frictional properties of the WC based IDB matrix are similar, while WS2 obtains a better self-lubricating performance than MoS2 . Highlights: MoS2 and WS2 are proposed to improve the drilling performance of diamond bit. Flexure strength and impact toughness are the mostly affected mechanical properties. Effects of MoS2 and WS2 on the mechanical and frictional properties are similar. WS2 yielded better test results than MoS2 due to its intrinsic characteristics.